2008
DOI: 10.1590/s0034-89102008005000041
|View full text |Cite
|
Sign up to set email alerts
|

Violência doméstica na gravidez: prevalência e fatores associados

Abstract: A high prevalence of different categories of domestic violence by an intimate partner during pregnancy was found as well as different factors associated with them. Appropriate mechanisms are necessary, particularly in primary health care, to identify and deal with domestic violence during pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
36
0
36

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(76 citation statements)
references
References 18 publications
4
36
0
36
Order By: Relevance
“…Except for the results detected in the municipality of Rio de Janeiro (61.7%) [10], in a rural community in South Africa (49%) [16] and in the Southern Appalachians (79.8%) [17], the prevalence rate of psychological violence (48.4%) detected in the Brisa prenatal cohort was higher than those reported in other studies, which ranged from 1.5% to 43% [4,8,11,12,18-24]. EPV and REPV prevalence rates were lower than those reported in only four of these publications [10,16,17,19].…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Except for the results detected in the municipality of Rio de Janeiro (61.7%) [10], in a rural community in South Africa (49%) [16] and in the Southern Appalachians (79.8%) [17], the prevalence rate of psychological violence (48.4%) detected in the Brisa prenatal cohort was higher than those reported in other studies, which ranged from 1.5% to 43% [4,8,11,12,18-24]. EPV and REPV prevalence rates were lower than those reported in only four of these publications [10,16,17,19].…”
Section: Discussionmentioning
confidence: 85%
“…Although some studies have pointed out this age range as being of higher risk for violence, a review of the literature has revealed that it was not possible to make this statement since the samples were mostly collected at hospitals or clinics and were not population based [4]. The results of investigations conducted in Michigan and in the municipality of Campinas, Brazil have shown that there was no association between psychological abuse and age of less than 20 years [8,12]. Durand and Schraiber [24] also detected no association between psychological violence by intimate partners and age of the pregnant woman.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a review of African studies revealed low SES as a risk factor for intimate partner violence [2]. In Brazil, two studies investigating the association between socioeconomic characteristics of pregnant women and intimate partner violence showed contrasting results [11,12]. In the WHO Multi-Country Study, high SES was a protective factor for intimate partner violence [13], but this finding was not replicated in the sample collected in São Paulo (Brazil) [14].…”
Section: Introductionmentioning
confidence: 99%
“…IPV during pregnancy has been associated with a variety of obstetrical risks, including late prenatal care, self-care deficits, abusive use of tobacco, alcohol and other substances, suicide attempts, depression, posttraumatic stress syndrome, sexually transmitted infections, unwanted pregnancies, pregnancy during adolescence, vulvovaginitis, bleeding, miscarriage, urinary tract infections, in addition to deficits in weight gain during pregnancy and violent deaths during pregnancy [2][3][4][5][6][7][8] . More severe consequences during pregnancy are described, including placenta previa, uterine rupture, hypertensive disorders, and chorioamnionitis, among others [9][10][11][12][13] . Severe maternal morbidity and IPV are both important disorders affecting maternal health.…”
mentioning
confidence: 99%